THE EFFECTIVENESS OF CANVA-BASED E-MODULES IN ISLAMIC EDUCATION LEARNING AT SMA NEGERI 1 TAMBANGAN - Muhammad Alwi Nasution; Ali Jusri Pohan; Anni marhamah; Aisah (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
This study aimed to determine the effectiveness of using Canva-based e-modules in Islamic Education (PAI) learning at SMA Negeri 1 Tambangan. The background of this research lies in the need to create innovative and interactive learning media that enhance students interest and understanding of Islamic Education materials. This qualitative research used observation, interviews, and documentation as data collection techniques. The data were analyzed through data reduction, dwasplay, and verification using source, technique, and time triangulation. The results showed that Canva-based e-modules improved students motivation, participation, and comprehension in PAI learning. The modules appealing vwasuals and multimedia elements such as images, videos, and animations made the material easier to understand and encouraged active learning. Supporting factors include accessibility and interactive design, while challenges include limited internet access and digital literacy among teachers and students. Overall, the Canva-based e-module was proven to be an effective innovative learning medium for improving the quality of Islamic Education at the senior high school level.